التفسير المقارن لسورة البقرة [من الآية211 إلى 230] - مسعودي نزيهة (University of Eloued جامعة الوادي, 2023)
يندرج هذا البحث تحت عنوان: التفسير المقارن لسورة البقرة من الآية " الحادية عشر بعد المئتين" إلى الآية "الثلاثون بعد المئتين"، فهو عبارة على دراسة تفسيرية تعتمد على المقارنة بين أقوال المفسرين في الآية الواحدة المختلفة اختلافا معتبراً، ومن هنا طرحت الإشكال الآتي: ما هي الكلمات أو العبارات أو المقاطع من الآيات التي اختلفت فيها آراء المفسرين اختلافا معتبراً في هذا المجال المحدود؟ وللإجابة على هذا الإشكال سلكت خطة تمثلت في ثلاث مباحث، المبحث الأول والذي يمثل الشق النظري، حيث، أدرجت فيه: التعريف بالتفسير المقارن، ثم نشأته وأهميته وخطواته، ثم الاختلاف الواقع في التفسير المقارن، وأما المبحث الثاني: فتناولت فيه مفهوم قواعد الترجيح، ثم قواعد الترجيح، وفي الأخير ختمت بحثي بمبحث تطبيقي ثالث: خصصته لدراسة الآيات من الآية الحادية عشر بعد المئتين إلى الآية الثلاثون بعد المئتين وفق خطوات التفسير المقارن، من النتائج التي توصلت اليها: أن معظم الآيات التي تناولتها بالدراسة تعتمد على أدلة صحيحة، إما من القرآن أو الأحاديث النبوية، أو في اللغة، كما أن الراجح فيها يكون غالبا باختيار أحد الأقوال أو الجمع بينهما. وقد وقفت في هذا البحث على تفسير تسعة مواضع رأيت أنها مختلفة اختلافا معتبرا وفسرتها تفسيرا مقارنا."This research falls under the title: Comparative interpretation of Surat Al-Baqarah from the “two hundred and eleventh” verse to the “two hundred and thirtieth” verse. It is an exegetical study based on comparison between the sayings of the commentators regarding one verse, which are significantly different, and from here I raised the following problem: What are the words, phrases, or passages of verses on which the opinions of commentators differed significantly in this limited area? To answer this problem, I followed a plan consisting of three sections. The first section, which represents the theoretical part, included: the definition of comparative interpretation, then its origin, importance and steps, then the difference occurring in comparative interpretation. As for the second section: I dealt with the concept of weighting rules, then The rules of weighting. Finally, I concluded my research with a third applied study: I devoted it to studying verses from the two hundred and eleventh verse to the two hundred and thirtieth verse according to the steps of comparative interpretation. In this research, I concluded the results, the most important of which are: that most of the verses that I studied depend on authentic evidence. Either from the Qur’an or the Prophet’s hadiths, or in the language, and the more correct one is often by choosing one of the sayings or combining them. In this research, I studied the interpretation of nine places that I saw as significantly different, and I interpreted them in a comparative manner."
مذكرة ماستر علوم قرآن
Keywords: التفسير المقارن –الترجيح –القران; comparative interpretation - weighting - the Qur’an